Various MPPT Modes and Dynamic Performance of Coupled Inductor Bipolar Multi-Output Converter With no Right Half Plane Zero - Kumar P.; Singh R.K. (My University, 2025)
This article proposes a coupled inductor bipolar multi-output converter (CI-BMC) and its four different operating modes for maximum power point tracking (MPPT) operations with improved dynamic performance during various transient and environmental conditions. The proposed CI-BMC is designed to supply bipolar dc and ac loads simultaneously from photovoltaic (PV) sources and effectively cater various dynamic conditions during MPPT operations in different modes. The proposed converter is designed using Cuk and SEPIC configuration, six mosfet switches, filter inductors and capacitors. The circuit is designed to eliminate right half plane zeros from it and therefore, can achieve wider bandwidth and better phase margin simultaneously which results in improved dynamic performance during MPPT operations. The challenges faced by the conventional multi-output converters for MPPT operation is also taken care in this article. Further, cross-regulation effect is reduced in case of CI-BMC which improves the converter dynamic stability substantially. Overall, CI-BMC provides a better interface for PV-based dynamic operations. Moreover, continuous input-output current and buck-boost capability also favor the MPPT operation. A laboratory prototype of 450 W is developed and implement using field programmable gate array based digital platform for dynamic performance and MPPT operations. © 1986-2012 IEEE.